PENGARUH KECERDASAN EMOSI DAN BUDAYA ORGANISASI TERHADAP KINERJA MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING PADA PEGAWAI DINAS PERTANAHAN DAN PENATAAN RUANG KABUPATEN KUTAI KARTANEGARA - Agus Sugianto; Dr. Ardi Paminto, MS; Dr. Irwan Gani, M.Si (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACT The Influence of Emotional Intelligence and Organizational Culture Against Performance through Satisfaction as Intervening Variables On Land Service Officials and Spatial Planning Regency of Kutai Kartanegara. his study was conducted to determine the partial influence of Emotional Intelligence (X1), and Organizational Culture (X2) on Satisfaction (Y1) and performance (Y2) of Land Office and Spatial Planning Official of Kutai Kartanegara Regency.In this research using Partial Least Squere Approach (PLS) with Equation Modeling (SEM) equation model using population of 132 (one hundred and thirty two) employees and freelance personnel. The results of this study concluded that the variables of Emotional Intelligence and Organizational Culture give a positive and significant impact on employee satisfaction on the Department of Land and Spatial Planning.  While Emotional Intelligence and Organizational Culture also give a positive influence on employee performance, but note that the influence is not significant. Variable Satisfaction of employee partially give positive and significant influence to performance of Land Service Official and Spatial Planning.It is known that the variables of Emotional Intelligence, Organizational Culture simultaneously have a positive effect on the performance of employees and significantly if through the intervening of employee satisfaction in the Land Agency and Spatial Planning.